2020
DOI: 10.3390/en13246623
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Deep Learning Models for Forecasting Time Series Data of Solar Irradiance and Photovoltaic Power

Abstract: Presently, deep learning models are an alternative solution for predicting solar energy because of their accuracy. The present study reviews deep learning models for handling time-series data to predict solar irradiance and photovoltaic (PV) power. We selected three standalone models and one hybrid model for the discussion, namely, recurrent neural network (RNN), long short-term memory (LSTM), gated recurrent unit (GRU), and convolutional neural network-LSTM (CNN–LSTM). The selected models were compared based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 60 publications
1
62
0
Order By: Relevance
“…To assess the forecast precision and compare the models, some validation metrics like Coefficient of determination (R 2 ), Root Mean Square Error (RMSE), mean absolute error (MAE), explained variance (EV), mean absolute percentage error (MAPE), Mean bias error (MBE), and Relative Mean bias error (rMBE) are used (Table II); where y t is concentration level of a pollutant,ŷ t is its corresponding forecasted values, and n is the number of data points [59], [60]. The more precise forecasting is, the lower RMSE, MAE, MBE and rMBE values and high R 2 , EV, and MAPE values are.…”
Section: Measurements Of Effectivenessmentioning
confidence: 99%
“…To assess the forecast precision and compare the models, some validation metrics like Coefficient of determination (R 2 ), Root Mean Square Error (RMSE), mean absolute error (MAE), explained variance (EV), mean absolute percentage error (MAPE), Mean bias error (MBE), and Relative Mean bias error (rMBE) are used (Table II); where y t is concentration level of a pollutant,ŷ t is its corresponding forecasted values, and n is the number of data points [59], [60]. The more precise forecasting is, the lower RMSE, MAE, MBE and rMBE values and high R 2 , EV, and MAPE values are.…”
Section: Measurements Of Effectivenessmentioning
confidence: 99%
“…The performance of these methods depends on the precise task, the available data as well as the data resolution and prediction window. Typically, the forecasts are obtained using a number of external sources including solar irradiance, wind, humidity and atmospheric pressure [14,26]. Sky-image-based techniques have been employed for time horizons of under one hour, while satellite-image-based techniques were found to be more suitable for the prediction of several hours ahead [27].…”
Section: Photovoltaic (Pv) Power Predictionmentioning
confidence: 99%
“…In addition, many studies only focus on the prediction of solar irradiance, since it is highly correlated to PV power. A detailed review of these methods can be found in [26] which also provides guidance on the suitability of different methods depending on the time horizon and the prediction window.…”
Section: Photovoltaic (Pv) Power Predictionmentioning
confidence: 99%
“…Some studies conclude that statistical models outperform ML models [ 10 ] while others state the opposite [ 11 , 12 ]. However, this interpretation may appear to be fairly simplistic without taking into account the dataset size [ 13 ], the variable being forecast [ 14 ], the time horizon [ 15 ], or the computational load [ 16 ]. Although historically, the forecasts have been dominated by statistical methods, over the last decade there has been a significant shift toward ML strategies [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The forecasting strategy developed in this paper, uses long short-term memory recurrent neural networks (LSTM-RNNs) and is based on an indirect approach in which the irradiance is forecasted first and the output power is calculated by using the PV model. LSTM-RNNs have been used in several works, achieving satisfactory results on account of their recurrent architecture, which includes memory units [ 16 ]. These allow the ANN to identify temporal patterns from the historical data of the forecast variable, thereby reducing the forecast error in comparison to other alternatives.…”
Section: Introductionmentioning
confidence: 99%